Inorganic Polymerization of Iron (lll) and Tungsten (Vl) in aqueous solution - Zenitagoya, Y. (2003)
In the present work we studied the chemical reactivity of cations Fe (III) and W (VI) in watery dissolution ,besides we propose the involved mechanism of reaction in thechemical process until the obtaining of the solid phase. The chemical reactions involved in the middle watery were studied using the Model of Charge Partial (MCP) whodescribes to the hydrolysis and condensation of cations Fe(III) and W(VI) dissolved in water and the chemical species that form when connecting with links H,O, OH and0₂. The polymerization sol-gel, as well as the formation of the solid phase until the obtaining of oxide of iron and tungsten oxide were studied by the techniques of VisibleSpectroscopy, Dispersion of Light, Infrared Spectroscopy, Transmission Electronic Microscopy and X-ray Diffraction. It were determined that the solid phases of the W(VI) and Fe (III) to 500 °C were monoclinic WO, and a-Fe.O, hematite respectively.